2020
DOI: 10.1186/s12890-020-1101-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and lung function outcomes in a cohort of children with severe asthma

Abstract: Background: Uncontrolled severe asthma in children is burdensome and challenging to manage. This study aims to describe outcomes in children with uncontrolled severe asthma managed in a nurse-led severe asthma clinic (SAC). Methods: This retrospective analysis uses data collected from children referred by a paediatric respiratory specialist to a nurse-led SAC for uncontrolled severe asthma between 2014 and 2019. The pre-clinical assessments included a home visit to assess modifiable factors that could be addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…While the magnitude of LCI and S cond changes observed is small and their clinical importance remains to be determined, it is possible that even small changes could have functional relevance. For instance, we and others have also shown that LCI is elevated, although mildly only, in many severe asthmatics as compared with those without severe asthma 43,44 . Several studies have also examined the utility of MBW in preschool asthma, and some 45,46 but not all 47 studies reported higher LCI values with an asthma diagnosis, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…While the magnitude of LCI and S cond changes observed is small and their clinical importance remains to be determined, it is possible that even small changes could have functional relevance. For instance, we and others have also shown that LCI is elevated, although mildly only, in many severe asthmatics as compared with those without severe asthma 43,44 . Several studies have also examined the utility of MBW in preschool asthma, and some 45,46 but not all 47 studies reported higher LCI values with an asthma diagnosis, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, we and others have also shown that LCI is elevated, although mildly only, in many severe asthmatics as compared with those without severe asthma. 43,44 Several studies have also examined the utility of MBW in preschool asthma, and some 45,46 but not all 47 studies reported higher LCI values with an asthma diagnosis, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…With a mass median aerodynamic diameter as low as 1 µm to 1.5 µm, the "extra-fine" ICS formulations can better penetrate small airways than traditional ICS. Observational studies have shown that the use of extra-fine particle ICS reduces exacerbations and improves asthma control [65]. Further studies are necessary to determine whether children with asthma and evidence of SAD would benefit from extra-fine ICS over conventional ICS.…”
Section: Impact Of Sad On Asthma Therapymentioning
confidence: 99%
“…Previous studies of VH in children mostly focused on cohorts with milder asthma and showed higher lung clearance index (LCI) in children with asthma compared to controls [2,3]; however, the average LCIs were usually still within the normal range [4,5]. Others did not stratify by severity [5][6][7] or focused solely on severe asthma [8].…”
Section: Communicated By Peter De Wintermentioning
confidence: 99%